Question 3: Can we diagnose asthma in children under the age of 5 years?. (February 2019) - Yang, C.L.; Gaffin, J.M.; Radhakrishnan, D.
Abstract: The diagnosis of asthma in children under five years has been controversial due to changing concepts of what true asthma is in this age group. Previous diagnostic algorithms that used clinical indices to predict the persistence of asthma symptoms or phenotypes based on asthma triggers do not predict which children will benefit from asthma medication. A pragmatic approach to asthma diagnosis in this age group is based on identifying signs and symptoms of reversible airflow obstruction and documenting their response to asthma medication. Hopefully, this approach will provide clearer guidance to clinicians and improve asthma morbidity in these young children.